2003
DOI: 10.1128/mcb.23.3.887-898.2003
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor 1 Is Required for Both Hormone-Dependent Chromatin Remodeling and Transcriptional Activation of the Mouse Mammary Tumor Virus Promoter

Abstract: The mouse mammary tumor virus (MMTV) promoter has been used as a model to study how the glucocorticoid receptor (GR) remodels chromatin to allow other transcription factors to bind and activate transcription. To dissect the precise role of nuclear factor 1 (NF1) in chromatin remodeling and transcriptional activation, we used linker-scanning mutants of transcription factor binding sites on the MMTV promoter. We compared the NF1 mutant MMTV promoter in the context of transiently transfected templates (transient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
38
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 60 publications
10
38
1
1
Order By: Relevance
“…Once recruited, this complex allows the initiation of the chromatin remodeling process, which may in turn stabilize the DNA binding of GR and NЈNRSF and promote the activation of gene transcription. This mode of cooperative function is consistent with recent studies demonstrating that in the glucocorticoid inducible MMTV promoter, recruitment of the BRG1 remodeling complex requires the simultaneous participation of GR and the transcription factor NF1 (52).…”
Section: Discussionsupporting
confidence: 77%
“…Once recruited, this complex allows the initiation of the chromatin remodeling process, which may in turn stabilize the DNA binding of GR and NЈNRSF and promote the activation of gene transcription. This mode of cooperative function is consistent with recent studies demonstrating that in the glucocorticoid inducible MMTV promoter, recruitment of the BRG1 remodeling complex requires the simultaneous participation of GR and the transcription factor NF1 (52).…”
Section: Discussionsupporting
confidence: 77%
“…A likely explanation is that these TFs act in different cellular contexts or have roles in vivo at these enhancers, such as remodeling chromatin, that are not required for activating transcription in our plasmid-based assay. Consistent with the latter notion, the list includes three Fox family TFs (Foxo4, Foxp3, and Foxd1), which act as pioneer factors that open chromatin during genomic enhancer activation (72)(73)(74), and two NFI TFs (NFIX and NFIC) that interact with histones (75,76) and contribute to remodeling of nucleosome architecture (77,78). The remaining two TFs (Myb and AP-2) have plausible roles in early adipocyte differentiation, regulating the final cell division (79,80) and repressing an alternate cell fate (81), respectively.…”
Section: Elements In the Sequence Flanking Pparγ Motifs Strongly Affectmentioning
confidence: 92%
“…Earlier studies demonstrated that MBD1 partners with the p150 subunit of chromatin assembly factor 1 to form a multiprotein complex that also contains HP1a, suggesting a role for MBD1 in methylation-mediated transcriptional repression and inheritance of epigenetically determined chromatin states (34). A role for NF1 in chromatin remodeling, in addition to its directly enhancing transcriptional effect, has been reported by Hebbar et al (35). NF1 interacts with a variety of coactivator or cosuppressor proteins in a cell-type-and/or promoter-specific manner (21).…”
Section: Figurementioning
confidence: 93%